Manufacturing Gender Inequality in the New Economy: High School Training for Work in Blue-Collar Communities. (August 2016) - Sutton, April; Bosky, Amanda; Muller, Chandra
Tensions between the demands of the knowledge-based economy and remaining, blue-collar jobs underlie renewed debates about whether schools should emphasize career and technical training or college-preparatory curricula. We add a gendered lens to this issue, given the male-dominated nature of blue-collar jobs and women's greater returns to college. Using the ELS:2002, this study exploits spatial variation in school curricula and jobs to investigate local dynamics that shape gender stratification. Results suggest a link between high school training and jobs in blue-collar communities that structures patterns of gender inequality into early adulthood. Although high school training in blue-collar communities reduced both men's and women's odds of four-year college enrollment, it had gender-divergent labor market consequences. Men in blue-collar communities took more blue-collar courses, had higher rates of blue-collar employment, and earned similar wages relative to otherwise comparable men from non-blue-collar communities. Women were less likely to work and to be employed in professional occupations, and they suffered severe wage penalties relative to their male peers and women from non-blue-collar communities. These relationships were due partly to high schools in blue-collar communities offering more blue-collar and fewer advanced college-preparatory courses. This curricular tradeoff may benefit men, but it appears to disadvantage women.